PERAPIHAN REARRANGEMENT SOUND SYSTEM INDOOR - Sunardi Sunardi; Jamal A. Rachman saprin; Rifa`i Harahap (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Markaz Hadits (MH) is a foundation that provides religious education with a core curriculum of memorizing the Quran and Hadiths of the Prophet Muhammad, at the level of junior high school (Tsanawiyah) and senior high school (‘Aliyah). The Tahfiz boarding school of Markaz Hadits Bilal bin Rabah Aliyah Legok is located in the village of Cirarab, where many of the residents work in factories, as sand and gravel transporters, farmers, and others. The boarding school is situated on a waqf land of approximately 800m2 with a mosque, classrooms, dormitories for students and teachers, as well as the school principal's residence. The mosque is the main facility for students to perform their worship and activities, and it also serves as a place of worship for the surrounding community. It is also a venue for conducting studies or lectures by speakers or teachers from various fields of knowledge, for students, the local community, as well as the school's mentors and supporters. To support these activities, a good audio sound system is required to amplify the adhan and other announcements, as well as for other activities. Therefore, an indoor and outdoor speaker system with optimal power and proper direction and placement is needed. The larger the space, the greater the power requirements, but it is important to consider power distribution. It is better to place several smaller speakers at specific points rather than one large speaker at a single point, and a suitable power amplifier to use is the Toa power amplifier. To optimize the indoor sound system of the mosque at the Tahfiz boarding school of Markaz Hadits Bilal bin Rabah Aliyah Legok, the Electrical Engineering Department of Pamulang University carried out a Community Service Program (PKM) entitled "Rearrangement of Indoor Sound System in the Mosque of the Tahfiz Boarding School of Markaz Hadits Bilal bin Rabah Aliyah Legok",